Meta‐Analysis of Randomized Clinical Trials Comparing Active Treatment with Placebo in Metastatic Neuroendocrine Tumors. (22nd July 2019) - Capdevila, Jaume; Hernando, Jorge; Perez‐Hoyos, Santiago; Roman‐Gonzalez, Alejandro; Grande, Enrique
Abstract: Background: Most guidelines still recommend active surveillance for patients with asymptomatic, unresectable neuroendocrine tumors (NETs). However, recent findings from several randomized placebo‐controlled trials suggest that most patients would benefit from active treatment. We conducted a meta‐analysis of pooled outcomes from clinical trials in which an active treatment arm was compared with placebo to determine whether active treatment provides a survival advantage. Materials and Methods: This meta‐analysis evaluated six trials that compared a medication with placebo in patients with an asymptomatic, metastatic NET. The trials were heterogenous with regard to the active medication (octreotide, lanreotide, sunitinib, everolimus, Lu‐Dotatate) and tumor localizations (gastrointestinal, pancreas, lung). Overall survival (OS) and progression‐free survival (PFS) for the placebo and active treatment arms were obtained from individual trial data and combined to obtain pooled outcomes. Results: The individual trials all reported significantly better PFS outcomes for active treatment. The pooled data confirmed this advantage. At months 3, 6, 12, 18, and 24, pooled PFS rates for the placebo and treatment arms, respectively, were 92.9% versus 96.9%; 54.3% versus 83.7%; 35.5% versus 68.5%; 25.1% versus 54.7%; and 17.7% versus 61.0%. OS was also higher in the active treatment groups. At months 6, 12, 24, 36, 48, and 60, OS rates (placebo vs. active treatment), respectively, were 88.1% versus 93.4%; 84.1% versus 86.2%; 67.4% versus 76%; 56.6% versus 64.4%; 49.9% versus 61.0%; and 41.7% versus 45.9%. Conclusion: This meta‐analysis confirms findings from recent clinical trials indicating that active treatment yields better survival outcomes than placebo. Importantly, these findings were obtained across a wide range of patient profiles and diverse medical treatments for metastatic NETs. Given the lack of reliable prognostic factors to determine a priori which patients are unlikely to benefit from active treatment, these findings support early treatment in most patients. Implications for Practice: Although most guidelines still recommend active surveillance for patients diagnosed with metastatic neuroendocrine tumors, the results of this meta‐analysis, together with recent data from key clinical trials, suggest that most patients could benefit from upfront active treatment. However, more data are needed to confirm this. Abstract : Neuroendocrine tumors (NETs) are slow‐growing and often asymptomatic and the optimal upfront management approach is controversial. Despite the lack of evidence‐based data, the watch‐and‐wait strategy is still included in clinical guidelines. The present article reports the results of a meta‐analysis of phase III clinical trials that have compared active treatment to placebo in patients with metastatic NETs.